Is asthma over-diagnosed in Cyprus? A clinical study at the outpatient's primary care level - Charis Armeftis; Marinos Lemessios; Christos Anastasiades; Christina Gratziou; Nikolaos Siafakas; Paraskevi Katsaounou; Petros Bakakos (Open Journal of Asthma - Peertechz Publications, 2022)
Background: Although asthma is a common disease accurate diagnosis is missing and it has been reported that often it is over or under-diagnosed. Aim: To investigate if a physician's diagnosis of asthma in Cyprus is correct by using a structured algorithm at the outpatient primary care level. Subjects and Methods: Sixty adults with a self-reported physician diagnosis of asthma, mean age of 47,8 years (29 males and 31 females) were included in the study. Medical history and physical examination, pre-post bronchodilation spirometry and methacholine bronchial challenge test was used to confirm or rule out the diagnosis as well as a three months follow-up. In addition, the cost of treatment was estimated. Results: Sixteen subjects (27%) had a positive pre-post bronchodilation spirometric test and were considered asthmatics. In 9 out of the 44 remaining subjects a positive Methacholine provocation test confirmed the diagnosis of asthma. The rest of the subjects (n = 35) went into a 3 months observational period during which only 2 showed asthmatic symptoms and were considered asthmatics by a second methacholine test that confirmed the diagnosis. Therefore, a correct asthma diagnosis was established in only 27(45%) of subjects. The annual average cost of medication for asthma confirmed the group was 313 euro/patient (171-454, 95% CI) and the average 2-year unnecessary (asthma ruled-out group) cost of treatment was approximately 297 euro/patient. (179-415, 95% CI). Conclusions: Physician-diagnosed asthma overestimates the actual prevalence of disease in adults in Cyprus since it was shown that more than half of the participants did not have Asthma. These individuals consume unneeded medications at a significant cost. Thus, the correct diagnosis of Asthma should be made by using more specific tests starting at the primary care level.